Parent involvement - Agency for Instructional Technology; Films for the Humanities (Firm) (Princeton, NJ : Films for the Humanities & Sciences, 2004)
Describes the parental role in bringing about change in schools and the role that parent involvement has in enhancing chances for success
DVD Format
Keywords: Education -- Parent participation; Parent-teacher relationships; School management and organization